(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Dietary pattern explains the overall diet; the food, food groups and nutrients included; their variety and combination. Breast cancer is the most prevalent cancer among women worldwide. Many risk factors for breast cancer contribute to personal habits, such as diet and exercise. Certain risk factors linked to lifestyle include decisions to have children and to take medicines containing hormones. Objectives of the study : To assess women’s dietary Habits, Foods Choices, and to find out the relation between demographic characteristics and breast cancer. Methodology: Adescriptive and analytic study, non-probability (a purposive sample) consist of (100) women was carried out at three Oncology Hospitals in Baghdad City, Iraq.The study group consist of(100) women divided in two groups the first one include (50) women as a (study group) that attending An oncology Hospitals and the second include (50) women as a (control group) that attending the Primary Health Care Centers. Results: women in both groups are consuming red meat with low frequency and amount than normal consumption . More than half of women with breast cancer are eating red meat one time per week (54%) while those without breast cancer are eating red meat two times per week (50%). Conclusion: women in both groups are consuming red meat with low frequency and amount than normal consumption Recommendation Avoid eating canned and processed red meat with preservatives and replaced it with fresh well cooked meat. Community orientation towards a healthy, balanced nutrition that contains the basic elements that the body needs without focusing on a specific food. Activation the role of media in increase the awareness of women in the community about healthy diet. Instruct women with breast cancer to follow a healthy diet guideline and avoid eating canned and processed red meat with preservatives during their treatment courses.